2007
DOI: 10.1016/j.febslet.2007.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal transport

Abstract: Transition metal transporters are of central importance in the plant metal homeostasis network which maintains internal metal concentrations within physiological limits. An overview is given of the functions of known transition metal transporters in the context of the unique chemical properties of their substrates. The modifications of the metal homeostasis network associated with the adaptation to an extreme metalliferous environment are illustrated in two Brassicaceae metal hyperaccumulator model plants base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
310
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(323 citation statements)
references
References 79 publications
(242 reference statements)
1
310
0
7
Order By: Relevance
“…A number of different transporters, such as Cation Diffusion Facilitator, Natural resistance-associated macrophage protein, ATPBinding Cassette, Zinc-and Iron-regulated-like Protein, and P-type ATPase, have been reported to be involved in the uptake, translocation, distribution, and homeostasis of nutrients (Hall and Williams, 2003;Krämer et al, 2007;Palmer and Guerinot, 2009). Among them, heavy metal-transporting P-type ATPase (HMA), the P 1B subfamily of the P-type ATPase superfamily, has been implicated in heavy metal transport (Williams and Mills, 2005;Grotz and Guerinot, 2006;Argüello et al, 2007;Burkhead et al, 2009).…”
mentioning
confidence: 99%
“…A number of different transporters, such as Cation Diffusion Facilitator, Natural resistance-associated macrophage protein, ATPBinding Cassette, Zinc-and Iron-regulated-like Protein, and P-type ATPase, have been reported to be involved in the uptake, translocation, distribution, and homeostasis of nutrients (Hall and Williams, 2003;Krämer et al, 2007;Palmer and Guerinot, 2009). Among them, heavy metal-transporting P-type ATPase (HMA), the P 1B subfamily of the P-type ATPase superfamily, has been implicated in heavy metal transport (Williams and Mills, 2005;Grotz and Guerinot, 2006;Argüello et al, 2007;Burkhead et al, 2009).…”
mentioning
confidence: 99%
“…It has been reported that multiple transporter proteins are present in plant root cells, which help in the uptake of essential elements (Verbruggen et al, 2009;Gall and Rajakaruna, 2013). Zinc-Regulated Transporter1/Iron-Regulated Transporter1 (ZRT1/IRT1)-like proteins are well known transporters responsible for the uptake of Zn 2+ by root cells (Kramer et al, 2007). Further movement of Zn from root to shoot is made possible by proteins of ZIP (Zinc-regulated transporter Iron-regulated transporter Proteins) and CDF (Cation Diffusion Facilitators) families (Verbruggen et al, 2009).…”
Section: Heavy Metal Transfer From Soil To Mustardmentioning
confidence: 99%
“…The elements Cd and Zn possess similar chemical properties and therefore both have parallel interactions in biological systems, which results in Cd transport by the members of the ZIP family transporters (Kramer et al, 2007). It is reported that Ca 2+ uptake channels in plant cells are also involved in Cd 2+ transportation (Perfus-Barbeoch et al, 2002).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…21 This essentiality/toxic duality of transition metals has resulted in the development of a complex homeostatic network for their acquisition and use in aerobic organisms. [22][23][24][25] In Arabidopsis thaliana, primary root uptake of the transition metals includes members of different families: NRAMP, ZIP and COPT ( Table 1). In all cases, the transport is induced under limiting conditions of the transition metals and in all cases, these transporters can mediate the influx of more than one transition metal.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%